Comparison of Two Different Approaches to Treat a Hallux Valgus Deformity: Intramedullary Self-Locked Plates and Herbert Screws - Zekeriya Okan Karaduman (Medicina, 2019)
Background and objectives: Hallux valgus is a complex deformity of the first metatarsophalangeal joint characterized by varus deformity of the first metatarsal bone, valgus deformity of the big toe, and lateral deviation of the extensor tendons and sesamoid bones. Several surgical methods have been described for correction of the deformity. Different materials have been used for the fixation of osteotomy. We compared the functional, radiological, and pain results of intramedullary self-locked plates and Herbert screws for the treatment of a hallux valgus deformity. Materials and Methods: Distal metatarsals were treated with self-locking intramedullary plate−screw systems in 18 feet from 12 patients (Group 1) and with Herbert screws in 18 feet from 12 patients (Group 2). The hallux valgus angle (HVA) and intermetatarsal angle (IMA) in patients of Group 1 and 2 were examined radiologically during the pre- and postoperative periods. We also determined the American Orthopedic Foot and Ankle Society (AOFAS), EQ-5D General Life Quality Scale, and Visual Analogue Scale (VAS) scores during the pre- and postoperative periods and compared the scores between groups. Results: Post hoc test results of HVA and IMA angles measured after the operation were significantly higher in Group 2 than in Group 1. In each group, the AOFAS scores during the preoperation period were significantly lower than those during the postoperation period (p < 0.001). According to the post hoc test results, the VAS scores after the operation were significantly higher in Group 2 than in Group 1 (p < 0.001). Conclusions: For the surgical treatment of hallux valgus, operations using self-locked plates compared to a single screw are superior in terms of providing rigid stability and for functional, radiological, and pain scores.